Physiology and molecular genetics of 17β-hydroxysteroid dehydrogenases - Andersson, Stefan; Moghrabi, Nabil (Steroids, 1997)
17β-Hydroxysteroid dehydrogenases (17β-HSDs) are enzymes involved in both the activation and inactivation of androgens and estrogens. 17β-HSD type 1 shows a high specificity for C 18 steroids and is the major isozyme in the granulosa cells of the ovary. Its role is to convert the inactive C 18 steroid estrone to the active estrogen estradiol, which in turn locally promotes maturation of the follicle. In contrast, attenuation of estradiol action in the glandular epithelium of the secretory endometrium is achieved by expression of the oxidative type 2 isozyme that inactivates estradiol to estrone. An interesting feature of 17β-HSD type 2 is that the enzyme also possesses 20α-HSD activity, i.e., it catalyzes the 20α-oxidation of the inactive C 21 steroid 20α-dihydroprogesterone to the active progestin progesterone. As the type 2 enzyme is also active on androgens, it may play a general role in the peripheral inactivation of androgens and estrogens, thus determining their steady-state levels in target tissues. The reductive 17β-HSD type 3 is predominantly expressed in the testis and converts the inactive C 19 steroid androstenedione to the active androgen testosterone. The importance of the type 3 enzyme in male steroid hormone physiology is underscored by the genetic disease 17β-HSD deficiency. Mutations in the 17β-HSD3 gene impair the formation of testosterone in the fetal testis and give rise to genetic males with normal male Wolffian duct structures but female external genitalia. To date, 15 mutations have been identified in 18 subjects with the disease.